Martha Gellhorn’s “Zoo in Madrid”: Hope and Betrayal in the Span-ish Civil War - Aguilera-Linde, Mauricio D. (Complutense Journal of English Studies, 2017)
Published in the late spring of 1937 as a literary journalism piece and included in Martha Gellhorn’s second volume of short fiction, Heart of Another (1941), “Zoo in Madrid” poses engaging questions about the journalist’s role as a war correspondent in the Spanish Civil War and her allegedly objective reportage method. In the following article, I propose to decode some of the elusive symbols of the story, built up on Hemingway’s iceberg principle of writing, in connection with its propaganda message. My contention is that the zoo, a clear symbol of the total institution, operates as a microcosmic reflection of the city under siege. However, Gellhorn’s portrayal of the animals’ conditions in the zoo is one which, unlike her contemporaries’ grim reports, enhances images of fertility and procreation immersed in an Edenic enclave that, however, fails to banish death and betrayal. In addition to a detailed revision of some of the pre-war, war and post-war reports of the Madrid zoo, I will endeavor to elucidate the biblical and literary allusions and echoes scattered in the story with a view to understanding the American journalist’s ambivalent view of the Spanish conflict.